Socio-cultural and operational determinants of local ecological knowledge on cetaceans among artisanal fishing communities in Gabon: Implications for marine governance - Judicaël Régis Kema Kema; Jean Damien Maloba Makanga; Guy Serge Bignoumba; Gianna Minton; Igor Akendengue Aken; Tim Collins; Jean Hervé Mve Beh; Brice Didier Koumba Mabert; Stephan Ntie; Omer Ntougou Ndoutoume; Vincent Ridoux (Marine Policy, 2026)

A whale apart: further evidence for genetic isolation of Arabian Sea humpback whales from other recognised subspecies - A. Rita Amaral; Stephen J. Gaughran; Melina I. Giakoumis; Andrew Willson; Gianna Minton; Robert Baldwin; Maia Sarrouf Willson; Suaad Al Harthi; Aida Al Jabri; Tim Collins; Koen Van Waerebeek; Howard C. Rosenbaum (Frontiers in Marine Science, 2026)
Genetic studies have differentiated three subspecies of humpback whales: Megaptera novaeangliae novaeangliae in the North Atlantic, M. n. australis in the Southern Hemisphere and M. n. kuzira in the North Pacific. However, these analyses did not include samples from the Arabian Sea humpback whale population (ASHW). Historic, behavioural, and previously published genetic data suggested that ASHWs are a discrete, isolated and resident population. This study provides further evidence of genetic uniqueness of the ASHWs by comparing samples collected in Oman with the three existing humpback whale subspecies. The morphological and genetic data obtained in this study confirmed the identification of the type specimen for Megaptera indica from Iraq as a humpback whale, closely related to contemporary ASHWs. Genetic differentiation between ASHWs and other subspecies were found (Fst values 0.1213-0.2441 and φ ST values 0.0831-0.6470). Together with the multiple lines of evidence for reproductive and behavioural isolation of this unique humpback whale population that does not undertake seasonal latitudinal migrations as do all other populations, this genetic data support the recognition of a fourth subspecies, which would be named for the type specimen from Iraq: Megaptera novaeangliae indica . Anthropogenic threats to ASHWs and their habitat are severe and escalating and there is a risk of extirpation. Population abundance is low with no evidence of increasing over the past two decades. The genetic differentiation of ASHWs may have been driven by a range of interdependent biogeographical and ecological factors coupled with behavioural adaptations over a period of ~43,000-113,000 years. Regionally coordinated conservation action is urgently needed to preserve this population’s unique genetic diversity.

Corrigendum to “Socio-cultural and operational determinants of local ecological knowledge on cetaceans among artisanal fishing communities in Gabon: Implications for marine governance” [Mar. Policy 191 (2026) 107160] - Judicaël Régis Kema Kema; Jean Damien Maloba Makanga; Guy Serge Bignoumba; Gianna Minton; Igor Akendengue Aken; Tim Collins; Jean Hervé Mve Beh; Brice Didier Koumba Mabert; Stephan Ntie; Omer Ntougou Ndoutoume; Vincent Ridoux (Marine Policy, 2026)

No place like home: assessing the multidimensional habitat use of endangered Arabian Sea humpback whales (Megaptera novaeangliae, Borowski 1781) with satellite telemetry - Andrew John Willson; Robert Baldwin; Simon Childerhouse; Salvatore Cerchio; Tim Collins; Tilen Genov; Ygor Geyer; Howard Gray; Brendan John Godley; Suaad Al Harthi; Aida al Jabri; Amy Kennedy; et al. (Frontiers in Marine Science, 2026)
The Arabian Sea humpback whale ( Megaptera novaeangliae ; ASHW) is understood to be the only population of this species that does not undertake long-range seasonal migrations between high- and low-latitude waters. Until recently, understanding the movements and range of individual ASHWs has relied mainly on comparisons of dorsal fin and tail-fluke images archived in photo-identification catalogues and on observations made during small-vessel surveys off the coast of Oman since 2000. The ASHW population is classified as Endangered by the IUCN Red List of Threatened Species, with an estimated 82 individuals off Oman’s coast (95% CI: 60–111), and faces increasing anthropogenic threats throughout its known range. To better understand the spatial ecology of this population, 14 Argos-enabled satellite tags were attached to ASHW off the Arabian Sea coast of Oman between February 2014 and December 2017. Individuals were tracked for a total of 749 days (mean=53, SD = 42, range=18–163 days) producing 484 days of depth-use data (mean=44, SD = 26, range=15-87). Home ranges extended along the western Arabian Sea coastline of northern Yemen and southern Oman, with a core area in the Gulf of Masirah (Oman). Switching state-space models revealed predominant area restricted search behavior (associated with breeding and foraging behavior) over continental shelf areas, with transiting movements occurring further offshore. The widest-ranging individual (a female, tag longevity 120 days) completed a round trip across the Northwest Indian Ocean between the Gulf of Masirah and the Gulf of Mannar (India). The track of this animal, and others along the coast of Oman, revealed an overlapping relationship between ecological drivers related to habitat use, including foraging and breeding, with fishing and shipping activities. The findings demonstrate the unique ecology of ASHW compared to other humpback whale populations and underscores the need for national and international authorities to incorporate these results into management initiatives to safeguard this small and Endangered population.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Deep-sea biotope classification using opportunistic sampling: insights for future management - Heidy Q. Dias; Kerstin Kröger; Andrew J. Wheeler; Riccardo Arosio; Audrey Recouvreur; Tim P. Le Bas; Isobel A. Yeo; Patrick C. Collins (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Assessing marine traffic and related pressures and threats to cetacean populations to support vessel management in the Mascarene Important Marine Mammal Area - Virginie Plot; Vanessa Estrade; Julie Martin; Thomas Rostaing; Tim Collins; Violaine Dulau (Marine Policy, 2025)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Advancing botanical safety: A strategy for selecting, sourcing, and characterizing botanicals for developing toxicological tools - Suramya Waidyanatha; Bradley J. Collins; Tim Cristy; Michelle Embry; Stefan Gafner; Holly Johnson; Josh Kellogg; Julie Krzykwa; Siheng Li; Constance A. Mitchell; Esra Mutlu; Sarah Pickett; et al. (Food and Chemical Toxicology, 2024)

Red‐list status and extinction risk of the world's whales, dolphins, and porpoises - Gill T. Braulik; Barbara L. Taylor; Gianna Minton; Giuseppe Notarbartolo di Sciara; Tim Collins; Lorenzo Rojas‐Bracho; Enrique A. Crespo; Louisa S. Ponnampalam; Michael C. Double; Randall R. Reeves (Conservation Biology, 2023)
To understand the scope and scale of the loss of biodiversity, tools are required that can be applied in a standardized manner to all species globally, spanning realms from land to the open ocean. We used data from the International Union for the Conservation of Nature Red List to provide a synthesis of the conservation status and extinction risk of cetaceans. One in 4 cetacean species (26% of 92 species) was threatened with extinction (i.e., critically endangered, endangered, or vulnerable) and 11% were near threatened. Ten percent of cetacean species were data deficient, and we predicted that 2–3 of these species may also be threatened. The proportion of threatened cetaceans has increased: 15% in 1991, 19% in 2008, and 26% in 2021. The assessed conservation status of 20% of species has worsened from 2008 to 2021, and only 3 moved into categories of lesser threat. Cetacean species with small geographic ranges were more likely to be listed as threatened than those with large ranges, and those that occur in freshwater (100% of species) and coastal (60% of species) habitats were under the greatest threat. Analysis of odontocete species distributions revealed a global hotspot of threatened small cetaceans in Southeast Asia, in an area encompassing the Coral Triangle and extending through nearshore waters of the Bay of Bengal, northern Australia, and Papua New Guinea and into the coastal waters of China. Improved management of fisheries to limit overfishing and reduce bycatch is urgently needed to avoid extinctions or further declines, especially in coastal areas of Asia, Africa, and South America.

Remote and non-invasive quantification of ‘Tattoo Skin Disease-Like’ dermatopathy in endangered Arabian Sea humpback whales using drone photography - Matthew S. Leslie; Louis Kant; Colin Perkins-Taylor; Marie-Françoise Van Bressem; Gianna Minton; Darryl MacDonald; Fredrik Christiansen; Maia Sarrouf Willson; Tim Collins; Robert Baldwin; Suaad Al Harthi; Andrew Willson (Mammalian Biology, 2022)

Missing Data in Sea Turtle Population Monitoring: A Bayesian Statistical Framework Accounting for Incomplete Sampling - Lucy C. M. Omeyer; Trevelyan J. McKinley; Nathalie Bréheret; Gaëlle Bal; George Petchell Balchin; Abdon Bitsindou; Eva Chauvet; Tim Collins; Bryan K. Curran; Angela Formia; Alexandre Girard; Marc Girondot; et al. (Frontiers in Marine Science, 2022)
Monitoring how populations respond to sustained conservation measures is essential to detect changes in their population status and determine the effectiveness of any interventions. In the case of sea turtles, their populations are difficult to assess because of their complicated life histories. Ground-derived clutch counts are most often used as an index of population size for sea turtles; however, data are often incomplete with varying sampling intensity within and among sites and seasons. To address these issues, we: (1) develop a Bayesian statistical modelling framework that can be used to account for sampling uncertainties in a robust probabilistic manner within a given site and season; and (2) apply this to a previously unpublished long-term sea turtle dataset (n = 17 years) collated for the Republic of the Congo, which hosts two sympatrically nesting species of sea turtle (leatherback turtle [ Dermochelys coriacea ] and olive ridley turtle [ Lepidochelys olivacea ]). The results of this analysis suggest that leatherback turtle nesting levels dropped initially and then settled into quasi-cyclical levels of interannual variability, with an average of 573 (mean, 95% prediction interval: 554–626) clutches laid annually between 2012 and 2017. In contrast, nesting abundance for olive ridley turtles has increased more recently, with an average of 1,087 (mean, 95% prediction interval: 1,057–1,153) clutches laid annually between 2012 and 2017. These findings highlight the regional and global importance of this rookery with the Republic of the Congo, hosting the second largest documented populations of olive ridley and the third largest for leatherback turtles in Central Africa; and the fourth largest non-arribada olive ridley rookery globally. Furthermore, whilst the results show that Congo’s single marine and coastal national park provides protection for over half of sea turtle clutches laid in the country, there is scope for further protection along the coast. Although large parts of the African coastline remain to be adequately monitored, the modelling approach used here will be invaluable to inform future status assessments for sea turtles given that most datasets are temporally and spatially fragmented.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Daniel J. Ingram; Margi Prideaux; Nicola K. Hodgins; Heidrun Frisch-Nwakanma; Isabel C. Avila; Tim Collins; Mel Cosentino; Lucy W. Keith-Diagne; Helene Marsh; Matthew H. Shirley; Koen Van Waerebeek; Maximin K. Djondo; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, in some places has been sustained for millennia, and can be an important source of nutrition, income, and cultural identity to communities. Yet, economic opportunities to exploit wildlife at higher levels have led to unsustainable exploitation of some species. In the literature, there has been limited focus on the exploitation of aquatic non-fish animals for food and other purposes. Understanding the scope and potential threat of aquatic wild meat exploitation is an important first step toward appropriate inclusion on the international policy and conservation management agenda. Here, we conduct a review of the literature, and present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We find that consumption of aquatic megafauna is widespread in coastal regions, although to varying degrees, and that some species are likely to be at risk from overexploitation, particularly riverine megafauna. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Comparative biogeography and the evolution of population structure for bottlenose and common dolphins in the Indian Ocean - Howard W. I. Gray; Ing Chen; André E. Moura; Ada Natoli; Shin Nishida; Shinsuke Tanabe; Gianna Minton; Louisa S. Ponnampalam; Muhammad S. Kiani; Ross Culloch; Mauvis Gore; Anna Särnblad; et al. (Journal of Biogeography, 2021)
Aim In the marine environment, where there are few physical boundaries to gene flow, there is often nevertheless intraspecific diversity with consequences for effective conservation and management. Here, we compare two closely related dolphin species with a shared distribution in the Indian Ocean (IO) to better understand the biogeographic drivers of their population structure. Location Global oceans and seas with a focus on the Indian Ocean Taxon Tursiops sp. and Delphinus sp. Methods Bayesian, ordination, assignment, statistical and phylogenetic analyses to assess phylogeography, connectivity and population structure using microsatellite and mitochondrial DNA genetic markers. Results Both Tursiops sp. and Delphinus sp. showed population structure across the western IO and, in each case, populations in the Arabian Sea (off India, Pakistan and Oman) were most differentiated. Comparisons with other populations worldwide revealed independent lineages in this geographic region for both genera. For T . aduncus , (for which multiple sites within the IO could be compared), Bayesian modelling best supported a scenario of expansion southwards following a bottleneck event resulting in differentiation between the northern and western IO. For Delphinus, the same pattern is even more pronounced. Populations in the Arabian Sea region of the north‐western IO show genetic isolation for each of the two genera, consistent with other studies of cetacean species in this region. Main conclusions We propose that changes in the intensity of the southwest monsoon during the climate cycles of the Pleistocene could have affected regional patterns of productivity and represent an important biogeographic driver promoting the observed patterns of differentiation and population dynamics seen in our focal species. Patterns of population genetic structure are consistent with phenotypic differences, suggesting an influence from distinct habitats and resources, and emphasising the need for effective conservation measures in this geographic region.

Cetacean Research and Citizen Science in Kenya - Michael Gilbert Mwango’mbe; Jane Spilsbury; Steve Trott; Judith Nyunja; Nina Wambiji; Tim Collins; Inês Gomes; Sergi Pérez-Jorge (Frontiers in Marine Science, 2021)
In 2011, several non-governmental and government agencies established the Kenya Marine Mammal Network (KMMN) to provide a platform for the consistent collection of data on marine mammals along the Kenyan coast, identify areas of importance and engage marine users and the general public in marine mammal conservation. Prior to the KMMN, relatively little was known about marine mammals in Kenya, limiting conservation strategies. The KMMN collects data nationwide through dedicated surveys, opportunistic sightings and participative citizen science, currently involving more than 100 contributors. This paper reviews data on sightings and strandings for small cetaceans in Kenya collated by the KMMN. From 2011 to 2019, 792 records of 11 species of small cetaceans were documented. The most frequently reported inshore species were the Indo-Pacific bottlenose dolphin and Indian Ocean humpback dolphin. Offshore species, included killer whales, short-finned pilot whale and long-snouted spinner dolphin. Indo-Pacific bottlenose dolphins, long-snouted spinner dolphins, striped dolphins and Risso’s dolphins were recorded through stranding reports. The efforts of the KMMN were disseminated through international meetings (International Whaling Commission, World Marine Mammal Conference), national status reports, outreach and social media. Data has also supported the identification of three IUCN Important Marine Mammal Areas and one Area of Interest in Kenya. Further research is needed to improve estimates of cetacean abundance and distribution, particularly in unstudied coastal areas, and to assess the extent of anthropogenic threats associated with fisheries, coastal and port development, seismic exercises and unregulated tourism. The expansion of the network should benefit from the participation of remote coastal fishing communities, government research agencies, tourism and seismic operations, among others. The KMMN demonstrated the value of dedicated and citizen science data to enhance marine mammal conservation strategies to boost awareness and eco-tourism and to bring the public and science closer together, promoting research and effective conservation efforts.

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Multiple processes drive genetic structure of humpback whale ( Megaptera novaeangliae ) populations across spatial scales - Francine Kershaw; Inês Carvalho; Jacqueline Loo; Cristina Pomilla; Peter B. Best; Ken P. Findlay; Salvatore Cerchio; Tim Collins; Marcia H. Engel; Gianna Minton; Peter Ersts; Jaco Barendse; et al. (Molecular Ecology, 2017)
Elucidating patterns of population structure for species with complex life histories, and disentangling the processes driving such patterns, remains a significant analytical challenge. Humpback whale ( Megaptera novaeangliae ) populations display complex genetic structures that have not been fully resolved at all spatial scales. We generated a data set of nuclear markers for 3575 samples spanning the seven breeding stocks and substocks found in the South Atlantic and western and northern Indian Oceans. For the total sample, and males and females separately, we assessed genetic diversity, tested for genetic differentiation between putative populations and isolation by distance, estimated the number of genetic clusters without a priori population information and estimated rates of gene flow using maximum‐likelihood and Bayesian approaches. At the ocean basin scale, structure is governed by geographical distance ( IBD P F ST 0.034–0.161; P

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

A Flood Risk Assessment of the LaHave River Watershed, Canada Using GIS Techniques and an Unstructured Grid Combined River-Coastal Hydrodynamic Model - Kevin McGuigan; Tim Webster; Kate Collins (Journal of Marine Science and Engineering, 2015)
A flexible mesh hydrodynamic model was developed to simulate flooding of the LaHave River watershed in Nova Scotia, Canada, from the combined effects of fluvial discharge and ocean tide and surge conditions. The analysis incorporated high-resolution lidar elevation data, bathymetric river and coastal chart data, and river cross-section information. These data were merged to generate a seamless digital elevation model which was used, along with river discharge and tidal elevation data, to run a two-dimensional hydrodynamic model to produce flood risk predictions for the watershed. Fine resolution topography data were integrated seamlessly with coarse resolution bathymetry using a series of GIS tools. Model simulations were carried out using DHI Mike 21 Flexible Mesh under a variety of combinations of discharge events and storm surge levels. Discharge events were simulated for events that represent a typical annual maximum runoff and extreme events, while tide and storm surge events were simulated by using the predicted tidal time series and adding 2 and 3 m storm surge events to the ocean level seaward of the mouth of the river. Model output was examined and the maximum water level for the duration of each simulation was extracted and merged into one file that was used in a GIS to map the maximum flood extent and water depth. Upstream areas were most vulnerable to fluvial discharge events, the lower estuary was most vulnerable to the effect of storm surge and sea-level rise, and the Town of Bridgewater was influenced by the combined effects of discharge and storm surge. To facilitate the use of the results for planning officials, GIS flood risk layers were intersected with critical infrastructure, identifying the roads, buildings, and municipal sewage infrastructure at risk under each flood scenario. Roads were converted to points at 10 m spacing for inundated areas and appended with the flood depth calculated from the maximum water level subtracted from the lidar digital elevation model.

Unravelling the complexities in high-grade rocks using multiple techniques: the Achankovil Zone of southern India - Richard J. M. Taylor; Chris Clark; Tim E. Johnson; M. Santosh; Alan S. Collins (Contributions to Mineralogy and Petrology, 2015)

The Agrodiversity Experiment: three years of data from a multisite study in intensively managed grasslands - Laura Kirwan; John Connolly; Caroline Brophy; Ole Baadshaug; Gilles Belanger; Alistair Black; Tim Carnus; Rosemary Collins; Jure Čop; Ignacio Delgado; Alex De Vliegher; Anjo Elgersma; et al. (Ecology, 2014)
Intensively managed grasslands are globally prominent ecosystems. We investigated whether experimental increases in plant diversity in intensively managed grassland communities can increase their resource use efficiency. This work consisted of a coordinated, continental‐scale 33‐site experiment. The core design was 30 plots, representing 15 grassland communities at two seeding densities. The 15 communities comprised four monocultures (two grasses and two legumes) and 11 four‐species mixtures that varied in the relative abundance of the four species at sowing. There were 1028 plots in the core experiment, with another 572 plots sown for additional treatments. Sites followed a protocol and employed the same experimental methods with certain plot management factors, such as seeding rates and number of cuts, determined by local practice. The four species used at a site depended on geographical location, but the species were chosen according to four functional traits: a fast‐establishing grass, a slow‐establishing persistent grass, a fast‐establishing legume, and a slow‐establishing persistent legume. As the objective was to maximize yield for intensive grassland production, the species chosen were all high‐yielding agronomic species. The data set contains species‐specific biomass measurements (yield per species and of weeds) for all harvests for up to four years at 33 sites. Samples of harvested vegetation were also analyzed for forage quality at 26 sites. These data should be of interest to ecologists studying relationships between diversity and ecosystem function and to agronomists interested in sustainable intensification. The large spatial scale of the sites provides opportunity for analyses across spatial (and temporal) scales. The database can also complement existing databases and meta‐analyses on biodiversity–ecosystem function relationships in natural communities by focusing on those same relationships within intensively managed agricultural grasslands.

Integrating multiple lines of evidence to better understand the evolutionary divergence of humpback dolphins along their entire distribution range: a new dolphin species in Australian waters? - Martin Mendez; Thomas A. Jefferson; Sergios‐Orestis Kolokotronis; Michael Krützen; Guido J. Parra; Tim Collins; Giana Minton; Robert Baldwin; Per Berggren; Anna Särnblad; Omar A. Amir; Vic M. Peddemors; et al. (Molecular Ecology, 2013)
The conservation of humpback dolphins, distributed in coastal waters of the Indo‐West Pacific and eastern Atlantic Oceans, has been hindered by a lack of understanding about the number of species in the genus ( Sousa ) and their population structure. To address this issue, we present a combined analysis of genetic and morphologic data collected from beach‐cast, remote‐biopsied and museum specimens from throughout the known Sousa range. We extracted genetic sequence data from 235 samples from extant populations and explored the mitochondrial control region and four nuclear introns through phylogenetic, population‐level and population aggregation frameworks. In addition, 180 cranial specimens from the same geographical regions allowed comparisons of 24 morphological characters through multivariate analyses. The genetic and morphological data showed significant and concordant patterns of geographical segregation, which are typical for the kind of demographic isolation displayed by species units, across the Sousa genus distribution range. Based on our combined genetic and morphological analyses, there is convincing evidence for at least four species within the genus ( S. teuszii in the Atlantic off West Africa, S. plumbea in the central and western Indian Ocean, S. chinensis in the eastern Indian and West Pacific Oceans, and a new as‐yet‐unnamed species off northern Australia).

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)